Leadership in post-compulsory education - Iszatt-White, Marian (Continuum, 2011)
The issue of leadership, the need for good, insightful and decisive leaders is a prominent theme in Education. Yet few can define exactly what leadership is. This book examines the phenomenon of leadership in post-compulsory education through the careful description and analysis of a long-term observational study of college principals at work. In contrast to other, more theoretical, attempts to understand leadership, this book develops an understanding of leadership by pointing to specific examples of what leaders actually do as they go about their everyday work of resolving organisational iss.